Pigmented Facial Contact Dermatitis to Benzyl Salicylate: A Comparative Histopathological and Immunohistochemical Study of the Involved Skin and the Positive Patch Test Site. (June 2019) - Zaaroura, Hiba; Bergman, Reuven; Nevet, Mariela J.
Abstract : Abstract: Pigmented contact dermatitis (PCD) is a noneczematous variant of allergic contact dermatitis, and benzyl salicylate is one of its causes. This type of PCD shows nonlichenoid interface dermatitis with pigment incontinence. We aimed to characterize the earliest histopathological changes of this reaction. A 51-year-old man presented with persistent facial eruption composed of hyperpigmented and hypopigmented macules due to exposure to benzyl salicylate present in his aftershave. The biopsies obtained from hyperpigmented and hypopigmented macules, and from the positive patch test site to benzyl salicylate, showed a nonlichenoid focal vacuolar interface dermatitis with mononuclear cells in the papillary dermis and around the pilosebaceous units, along with melanophages. A MART-1 immunostain showed intact melanocytes in all 3 biopsies. A Fontana–Masson stain demonstrated intact melanin in the basal cell layer of a facial hyperpigmented macule and the patch test site, but melanin was reduced in the biopsy taken from a hypopigmented facial macule. There were more epidermal and dermal CD1a+ Langerhans cells in the patch test biopsy than in the other 2 biopsies. Most of the mononuclear cells were CD3+. The CD4+ to CD8+ ratio was approximately 1:1 in the facial macules; yet, CD4+ cells outnumbered CD8+ cells in the patch test biopsy. There were a few TIA-1+ cells in all 3 biopsies. In conclusion, the earliest histopathological and immunophenotypical events in PCD due to benzyl salicylate are similar to those of longer-standing lesions, i.e., a nonlichenoid focal interface dermatitis involving the epidermis and pilosebaceous unit, along with dermal melanophages.